French Lessons in Late-Medieval England : The Liber Donati and Commune Parlance. - Critten, Rory G. (Amsterdam : Arc Humanities Press, 2023)
These teaching and reference materials paint a vivid picture of the kinds of French that medieval English learners might desire to wield and of the high levels of fluency they could achieve.
[12. Turning away a beggar] -- [13. Two companions at an inn] -- [14. Dialogues between traders] -- [15. Asking the time and the way] -- [16. Asking for lodging -- giving a message] -- [17. At the scrivener's] -- [18. Asking the way -- delivering a present] -- [19. Different greetings according to the time of day] -- [20. Dialogue with an ill man] -- [21. Dialogue with a foreigner] -- [22. A tailor and his new master] -- [23. Two companions at an inn again] -- Commentary and Notes -- Textual Notes -- Bibliography.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books